Reconciliation Analysis of Passengers Suspected of Carrying Dangerous and Prohibited Goods at Komodo Labuan Bajo Airport Security Checkpoint - Modestania Fransiska Raja; Sri Sutarwati (CV. Rayyan Dwi Bharata, 2023)
Aviation Security (AVSEC) has an important role in security and safety in aviation, starting from checking passengers and their luggage, so that acts of disturbance that violate the law do not occur. This study aims to find out how the reconciliation process is for passengers suspected of carrying dangerous and prohibited goods at the Security Check Point (SCP) of Komodo Labuan Bajo Airport, as well as the socialization carried out by the airport about what dangerous and prohibited goods may not be carried by airplane passenger. This study uses qualitative research. The subjects in this study were Aviation Security (AVSEC) officers at Komodo Labuan Bajo Airport. The results of this study were obtained using interviews, observation and documentation carried out during the research. After obtaining the necessary data the researcher will process the data into a discussion and make a conclusion and suggestions. Based on the research results obtained by researchers, the reconciliation process for passengers suspected of carrying dangerous and prohibited goods at the Security Check Point of Komodo Labuan Bajo Airport starts from Security Check Point (SCP) 1 and 2 before passengers and their luggage enter the restricted security area, after it goes through an inspection process using a tool, if dangerous and prohibited items are detected, the officer directs passengers to a special inspection room, and there the Aviation Security officer explains that these items are prohibited from being carried, and if they can be carried, they must be in checked baggage and vice versa in cabin baggage . The socialization carried out by the Komodo Labuan Bajo Airport took the form of holding a committee meeting and inviting several agencies that deal directly with the community such as the TNI-POLRI and the Tourism Office, as well as installing standing banners containing prohibitions on what dangerous and prohibited goods may not be carried by airplane passenger.